2019
DOI: 10.4067/s0718-221x2019005000311
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetría en la madera de Prosopis alba

Abstract: El algarrobo blanco (Prosopis alba) se caracteriza por sus excelentes propiedades física-mecánicas en su madera, lo cual la hace muy apreciable en la industria del mueble. El color es un rasgo importante en ciertos usos de la madera, e incide en su calidad. El objetivo de este trabajo fue evaluar la variación colorimétrica de la madera entre sitios, sección y región de la madera y correlacionar parámetros colorimétricos con rasgos morfométricos del árbol. Las muestras se extrajeron de tres rodales naturales (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The light colour of marupa wood is explained by the high L* values of 82,83 the marked presence of yellow pigment (b* 22,72) and low presence of the red pigment (a* 3,51). Similar behavior of L* variation in relation to yellow and red pigments was correlated in a work by Cisneros et al (2019) in analyzing Prosopis alba wood. The high h* value of 81,23 positions the colour of this wood near the b* axis, confirming the great influence of the b* coordinate on the colour characterization of the studied wood.…”
Section: Colorimetrysupporting
confidence: 77%
“…The light colour of marupa wood is explained by the high L* values of 82,83 the marked presence of yellow pigment (b* 22,72) and low presence of the red pigment (a* 3,51). Similar behavior of L* variation in relation to yellow and red pigments was correlated in a work by Cisneros et al (2019) in analyzing Prosopis alba wood. The high h* value of 81,23 positions the colour of this wood near the b* axis, confirming the great influence of the b* coordinate on the colour characterization of the studied wood.…”
Section: Colorimetrysupporting
confidence: 77%
“…Differences between heartwood and sapwood have been described in other species related to growing conditions. In Prosopis alba, Cisneros et al (2019) found a distinction between and inside trees and observed darker heartwood at sites with more precipitation. Sotelo Montes et al (2013) also described the influence of environment on wood color.…”
Section: Discussionmentioning
confidence: 90%
“…These results corroborate literature that describe variation in colorimetric parameters from transversal to radial or tangential sections in native forest, as Vieira et al (2019) which reported a tendency of parameter b* to be smaller in transversal sections in some Myrtaceae species and verified the influence of each species. Evaluating wood from different sites, native and planted forest, of Prosopis alba Griseb, Cisneros et al (2019) reported that transversal sections were darker in heartwood while in sapwood there were no differences among sections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations